2017
DOI: 10.1111/mmi.13757
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for substrate selection by the translocation and assembly module of the β‐barrel assembly machinery

Abstract: The assembly of proteins into bacterial outer membranes is a key cellular process that we are only beginning to understand, mediated by the β-barrel assembly machinery (BAM). Two crucial elements of that machinery are the core BAM complex and the translocation and assembly module (TAM), with each containing a member of the Omp85 superfamily of proteins: BamA in the BAM complex, TamA in the TAM. Here, we used the substrate protein FimD as a model to assess the selectivity of substrate interactions for the TAM r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 54 publications
2
31
0
Order By: Relevance
“…S9 and S10). We recently calculated the gate-opening PMF for TamA (28), which also has a kinked C-terminal strand; we found similarly low PMF values compared with NgBamA (see SI Appendix, Fig. S6).…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…S9 and S10). We recently calculated the gate-opening PMF for TamA (28), which also has a kinked C-terminal strand; we found similarly low PMF values compared with NgBamA (see SI Appendix, Fig. S6).…”
Section: Resultsmentioning
confidence: 75%
“…Second, equilibrium MD simulations indicated that a separation between the β-strands at the barrel seam could occur, producing a so-called "lateral gate" between the hydrophobic membrane environment and the aqueous β-barrel lumen. Recently, this lateral gate was also shown to exist in TamA, which is believed to have arisen via gene duplication of BamA and assists in the assembly of some OMP substrates (e.g., autotransporters like EhaA and Ag43) (26)(27)(28). Third, a thin hydrophobic region in BamA near the lateral gate produced a destabilized membrane, which may decrease the barrier for OMP integration (29)(30)(31).…”
mentioning
confidence: 99%
“…TamA, a member of the Omp85 protein superfamily, forms a 16‐stranded β‐barrel like BamA and contains three N‐terminal POTRA domains. The three‐dimensional structure of TamA and molecular dynamics simulations reveal that β‐strands 1 and 16 are only partially paired and may form of a lateral gate that, as proposed for BamA, opens to catalyze a protein translocation process (Gruss et al ., ; Bamert et al ., ). TamA is co‐expressed with TamB, a periplasmic protein connected to the IM via an N‐terminal signal anchor (Selkrig et al ., ).…”
Section: Role Of the Tam In Autotransporter Assemblymentioning
confidence: 97%
“…Thus, it cannot be excluded that, given identical experimental settings, all autotransporters would reveal a similar BAM complex‐only or BAM complex/TAM dependent biogenesis. In addition, the models of the BAM complex/TAM cooperation discussed above could also be relevant to further reactions of OM protein assembly that appear to depend on both translocases, such as the biogenesis of the chaperone‐usher secretory pore of type I fimbriae, FimD (Stubenrauch et al ., ; Bamert et al ., ).…”
Section: Role Of the Tam In Autotransporter Assemblymentioning
confidence: 97%
“…Previous structural and phylogenetic analyses (Heinz & Lithgow, 2014) suggested a model for the evolution of TamA through a gene duplication of bamA followed by an evolutionary process of sub-functionalization. This process of gradual change in one copy of the gene provides the means to ultimately encode a protein (TamA) that performs its function in a significantly different way (Shen et al, 2014, Selkrig et al, 2015, Bamert et al, 2017, to facilitate the process of outer membrane protein assembly in collaboration with BamA (Albenne & Ieva, 2017). In principle, bamK might represent an early event on an equivalent trajectory toward a further sub-functionalization.…”
Section: Discussionmentioning
confidence: 99%